Clinicopathological analysis of ovarian tumors in perimenopausal women: A study in a rural teaching hospital of eastern India - Phukan, Jyoti Prakash; Sinha, Anuradha; Sardar, Rakhi; Guha, Paulami (Bangladesh Journal of Medical Science, 2013)
Introduction: Ovarian tumors are important in perimenopausal women as they are more likely to be malignant. Aim: The aim was to study the various histological pattern of ovarian tumors and their clinical presentation in perimenopausal age group. Materials and Methods: The study was carried out in the departments of Gynaecology and Obstetrics and Pathology in a teaching hospital for two years from June 2007 to May 2009. All patients presented with ovarian tumors of perimenopausal age group (40-50 years) were included. Detailed clinical information, radiological findings and histopathological reports were recorded. Results: A total 52 ovarian tumors were included in this study. Most common histological types were surface epithelial tumors (92.3%), out of which 54.2% were benign, 41.7% were malignant and 4.2% were borderline. Serous cystadenoma was the most common benign tumor and serous cystadenocarcinoma was the commonest malignant tumor. Abdominal discomfort was the commonest presenting symptom both in benign and malignant tumors (85.7% and 45.4% respectively). Most of the malignant tumors were presented in stage III (50%), followed by stage II (27.3%). Conclusion: In this study, we found a relatively higher proportion of ovarian malignancies. So, any ovarian tumor in perimenopausal age group is more likely to be malignant and that require a thorough evaluation and management. Further research should be advocated in this field. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 263-268 DOI: http://dx.doi.org/10.3329/bjms.v12i3.12232